2009
DOI: 10.1016/j.ceca.2008.12.001
|View full text |Cite
|
Sign up to set email alerts
|

IP3 receptor subtype-dependent activation of store-operated calcium entry through ICRAC

Abstract: The store-operated, calcium release-activated calcium current I CRAC is activated by the depletion of inositol 1,4,5-trisphosphate (IP 3 )-sensitive stores. The significantly different dose-response relationships of IP 3 -mediated Ca 2+ release and CRAC channel activation indicate that I CRAC is activated by a functionally, and possibly physically, distinct sub-compartment of the endoplasmic reticulum (ER), the so-called CRAC store. Vertebrate genomes contain three IP 3 -receptor (IP 3 R) genes and most cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
(39 reference statements)
1
15
0
Order By: Relevance
“…5B). However, the DT40 KO cells have previously been shown to activate endogenous I CRAC when stores are depleted independent of IP 3 receptors [40]. To confirm these previous observations we applied 10 µM thapsigargin (Tg) at 60 s resulting in I CRAC development (Fig.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…5B). However, the DT40 KO cells have previously been shown to activate endogenous I CRAC when stores are depleted independent of IP 3 receptors [40]. To confirm these previous observations we applied 10 µM thapsigargin (Tg) at 60 s resulting in I CRAC development (Fig.…”
Section: Resultssupporting
confidence: 57%
“…As DT40 cells develop very small I CRAC , we optimized experimental conditions by increasing the external CaCl 2 concentration to 20 mM and expanding the voltage ramp to −150 mV, extracting current amplitudes at −130 mV [40]. Furthermore internal MgCl 2 concentration was increased to 3 mM to inhibit endogenous TRPM7 currents.…”
Section: Resultsmentioning
confidence: 99%
“…According to this model, that has been supported by convincing experimental data in a number of cell types [see 90, for a recent review], only ATP engages the Ca 2+ storage site which lies in close apposition to the PM in ECFCs [25]. In this view, it has been shown that InsP 3 R-2 and InsP 3 R-3, but not InsP 3 R1, drive SOCE activation in avian B cells [93], while InsP 3 R-1 is the main isoform linked to Stim1 translocation in H4IIE liver cells [94]. ECFCs express all the three known InsP 3 R subtypes: future work will have to assess which of them is selectively coupled to SOCE in these cells.…”
Section: Store-operated Ca 2+ Entry In Endothelial Colony Forming Celmentioning
confidence: 72%
“…Outside the immune system, these cells include (but are not limited to) vascular endothelial (88–90) and smooth muscle cells (91, 92), pancreatic acinar cells (93), hepatocytes (94), and adrenal chromaffine cells (95). In the immune system, SOCE and I CRAC have been observed in many different cell types of the lymphoid and myeloid lineage such as T cells (3), mast cells (4), B cells (96–98), dendritic cells (12), macrophages (99), NK cells (100), and neutrophils (11). It is likely that SOCE plays a role in other cell types in the immune system as well and contributes to proper innate and adaptive immune responses.…”
Section: Stim and Orai Expression In Cells Of The Immune Systemmentioning
confidence: 99%